2021
DOI: 10.1007/s00330-021-08140-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of simultaneous [68Ga]Ga-PSMA-11 PET/MR versus PET/CT in patients with biochemically recurrent prostate cancer

Abstract: Objectives PSMA-PET has become the PET technique of choice to localise the site of biochemically recurrent prostate cancer (PCa). With hybrid PET/MRI, the advantages of MRI are added to molecular characteristic of PET. The aim of this study was to investigate the incremental value of PET/MR versus PET/CT in patients with biochemically recurrent PCa by head-to-head comparison. Methods Thirty-four patients with biochemically recurrent PCa were prospectively included. They underwent [ 68 Ga]Ga-PSMA-11 PET/CT, fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The PET/MRI acquisition consisted of a TOF PET scan of 5 min per bed position (5–6 bed positions per patient) with simultaneous recordings of axial DW-MRI images, followed by T1- and T2-weighted imaging. Detailed acquisition parameters of the MRI sequences (DWI, T1 and T2) can be found in Supplemental Information (see also Jentjens et al 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…The PET/MRI acquisition consisted of a TOF PET scan of 5 min per bed position (5–6 bed positions per patient) with simultaneous recordings of axial DW-MRI images, followed by T1- and T2-weighted imaging. Detailed acquisition parameters of the MRI sequences (DWI, T1 and T2) can be found in Supplemental Information (see also Jentjens et al 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Due to small numbers of patients, statistical power has been limited in these studies. In 34 patients, Jentjens et al [48 ▪▪ ] found that 68 Ga-PSMA-11 PET/MRI performed at least as well as PET/CT, and in this small study, although not statistically significant, PET/MRI found more patients with positive lesions and more lesions over all (88 versus 81), including lymph nodes (57 versus 51) and bone metastases (16 versus 15), than by PET/CT despite not including mpMRI sequences; further, PET/MRI was more sensitive for lymph node metastases than MRI or CT alone. In a study of 62 patients with recurrence and 150 lesions, 68 Ga-PSMA-11 PET/MR detected 11 lesions not seen by PET/CT, including five lymph nodes and six local recurrences, with the latter being statistically significant; further, interpreting PET/MR resulted in higher diagnostic confidence than PET/CT [49 ▪▪ ].…”
Section: Pet Imagingmentioning
confidence: 98%
“…There were still 55 studies for full-text screening, and another 18 were disqualified due to the following reasons: non-English studies (n = 3); cannot extract positivity rate data (n = 7); and different radiotracers (n = 8). 37 studies that satisfied the criteria for the meta-analysis were finally included, including 25 articles for 68 Ga-PSMA-11 PET/CT (14-38) and 13 articles for 68 Ga-PSMA-11 PET/MRI (4,26,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). One of the studies included not only 68 Ga-PSMA-11 PET/CT but also 68 Ga-PSMA-11 PET/MRI.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%